The Use of Social Media and its Effect on University Students' Academic Skills in Iraqi Kurdistan Region (Raparin Journal of Humanities (RJH), 2021)
In recent decades, the use of social media has encountered a rapid growth. This progress made social media a very popular medium of communication among college students. In fact, these online mediums can be a good method to share the knowledge among students and with their lectures. However, extreme use of social media can affect student’s academic performance and skills. Social media platforms have developed significantly in the variety and type of its platforms and the variety of services they have provided to the users. This social media development has had a great impact on human life around the world, particularly the learning process among the students.The present study examines the effects of social networks on university students' academic skills in Iraqi Kurdistan Region. The sample involved 653 responses from the universities of Raparin and Sulaimani Polytechnic in Kurdistan Region - Iraq. The data of the study has been analyzed using content analysis methods.According to the study’s results there is a statistically significant correlation between Use of social media and academic skills and there is a strong positive correlation between Use of social media and academic skills which is (0.809) and that the significance value is (0.000).Then, the value of R Square for this analysis, is (0.655), this means that 65.5% of the variance of academic skills must be explored in Use of social media, and the other variables (34.5%) are due to random error.